Chemical soil attributes evaluated by multivariate techniques and geostatistics in the area with agroforestry and sugarcane in HumaitÁ, AM, Brazil - de Aquino, Renato Eleoterio [UNESP]; Campos, Milton Cesar Costa; Soares, Marcelo Dayron Rodrigues; de Oliveira, Ivanildo Amorim [UNESP]; Franciscon, Uilson; Silva, Douglas Marcelo Pinheiro; Cunha, José Maurício (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2016)
Studies on the spatial behavior of soil attributes in the Amazon region are still very incipient. In this sense, the objective of this work was to evaluate the chemical attributes through multivariate techniques and geoestatistics in the area with agroforestry and sugarcane in Humaitá, AM, Brazil. The study was carried out in a farm in Humaitá city, Amazonas State. The studied area was divided into 70.00 m x 70.00 m meshes with a regular spacing of 10 m, totaling 64 points and then, soil samples were collected at 0.0-0.2 m and 0.4-0.6 m depths. We performed chemical analyses of the attributes of soil. Then, it was applied descriptive statistics, multivariate and geostatistics. In conclusion, our findings suggest that for most of the chemical attributes was observed spatial dependence in both areas, with DSD varying from weak to moderate, with prevalence of the weak one. The multivariate analysis was efficient in the selection of chemical soil attributes that best represented the agroforestry environments and sugarcane. The results of this study will serve as a basis for further studies on these environments and other systems within the region; moreover serving as a basis for agricultural planning aiming a better environmental sustainability.
Atributos químicos do solo avaliados por técnicas multivariadas e geoestatísticas em área com agrofloresta e cana-de-açúcar em Humaitá, AM, Brasil
Keywords: Soil attributes; Southern Amazonas; Spatial variability